Acute fatty liver of pregnancy: a case report - Putu Gede Agus Surya Mahardika; Aditya Prabawa; Ketut Suardana (DiscoverSys Inc., 2020)
Introduction: Acute fatty liver of pregnancy (AFLP) is rare but potentially lethal complication. AFLP characterized by microvascular fatty infiltration of hepatocytes without any inflammation or necrosis.Case Presentation: A 37-year-old multigravida with 29 weeks period of gestation came with chief complains of acute jaundice, nausea, malaise and anorexia since 7 days ago. On examination, her eyes were icteric and her motor power was decreased on both extremities. Abdominal examination showed fetus in cephalic presentation with normal fetal heart rate. There was no opening and effacing of cervix. The ECG result showed prolonged QT interval. She had elevated liver enzyme, decreased renal function, electrolyte imbalance, hypoalbuminemia and hypercholesterolemia. Abdominal ultrasound was within normal limit. Patient was then assessed with differential diagnosed of AFLP, acute hepatitis and HELLP syndrome. She was treated conservatively with ferrous sulfate, high carbohydrate diet, KSR once daily, CDR once daily and Bisoprolol 1.25mg once daily. Â Three months later patient delivered a healthy baby boy via caesarian section due to premature rupture of membrane.Conclusion: Since AFLP is a medical and obstetric emergency, early recognition and prompt treatment improves both maternal and fetal survival.